2016
DOI: 10.1128/jvi.02903-15
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Surface Antigen Activates Myeloid Dendritic Cells via a Soluble CD14-Dependent Mechanism

Abstract: Hepatitis B virus (HBV) infection can cause chronic liver disease, which is associated with increased risk of liver cirrhosis, liver failure, and liver cancer. Clearance of HBV infection requires effective HBV-specific immunity; however, the immunological mechanisms that determine the development of effective HBV-specific immunity are poorly understood. Dendritic cells (DC) play a pivotal role in the regulation of antiviral immunity. Here, we investigated the interaction between HBV surface antigen (HBsAg), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…Possibly, previous studies reporting increased sCD14 levels in CHB included a subset of CHB patients with more severe liver disease, while in our cohort, ~86% treatment‐naive CHB patients have a relative low fibrosis level (<F2 by fibroscan). Furthermore, we here demonstrate that ethnicity influences sCD14 levels which was reported before in rheumatoid arthritis patients and we previously reported the same for age, indicating that also these parameters may be a cause of discrepancy.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Possibly, previous studies reporting increased sCD14 levels in CHB included a subset of CHB patients with more severe liver disease, while in our cohort, ~86% treatment‐naive CHB patients have a relative low fibrosis level (<F2 by fibroscan). Furthermore, we here demonstrate that ethnicity influences sCD14 levels which was reported before in rheumatoid arthritis patients and we previously reported the same for age, indicating that also these parameters may be a cause of discrepancy.…”
Section: Discussionsupporting
confidence: 86%
“…We previously demonstrated that HBsAg can activate Kupffer cells . In addition, we showed that HBsAg‐sCD14 complexes exist in serum of CHB patients and that HBsAg induces dendritic cell activation in a CD14‐dependent manner . Preliminary experiments suggest that PEG‐IFN stimulation may trigger sCD14 release by cultured Kupffer cells especially when HBsAg is present (unpublished data).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In fact, the soluble fraction of CD14, bound to HBsAg, could be responsible for this activation [36]. The fact that the lipid moiety of HBsAg subviral particles is instrumental for this activation represents an interesting finding.…”
Section: Interplay Between Hbv and Innate Immunity: Basic Insightsmentioning
confidence: 99%